The Influence of Biosaka as an Elisitor to Increase Productivity of Food Crops Pakcoy (Brassica rapa L.) as Eco-Friendly Agricultural Innovation - Akbar, Ali; Khairunnisa, Khairunnisa; Meutiasari, Cut Salsabila; Sari, Muliani Tiana; Mahyuny, Siska Rita (Jurnal Biologi Tropis, 2024)
The pakcoy plant (Brassica rapa L) belongs to the type of mustard vegetable that is easy acquired and quite economical. This is enough to increase the community's need forpakcoy plant. Rising fertilizer prices are forcing farmers to look for alternatives others to supply nutrients for plants. Biosaka is a biological elisitor that can increases productivity in plants. The purpose of this study is to find out The influence of biosaka on pakcoy plants. This research uses quantitative methods with this type of experimental research. The experimental design in this study is group random design (RAK) with parameters namely stem height, leaf width, number leaves and weight of pakcoy. The results of this study show that there is an influence that Significant to the productivity of pakcoy plants given additional biosaka with analysis data ANOVA. Where In the third treatment, the significant effect was more visible.